A one-season prospective study of injuries and illness in elite junior tennis - Pluim, B. M.; Loeffen, F. G. J.; Clarsen, B.; Bahr, R.; Verhagen, E. A. L. M. (Scandinavian Journal of Medicine & Science in Sports, 2016)
The objective of this study was to estimate the incidence and prevalence of injury and illness among elite junior tennis players. A cohort of 73 players (11-14 years) in the 2012-2013 Dutch national high-performance program was followed for 32 weeks; all participants completed the study. The OSTRC Questionnaire on Health Problems was used to record self-reported injuries and illnesses and to record training and match exposure. Main outcome measures were average prevalence of overuse injury and illness and incidence density of acute injury. On average, players practiced 9.1?h/week (SD 0.6; range 2.3-12.0) and had 2.2 h of match play (SD 0.6; range 2.3-12.0). During the course of the study, 67 players reported a total of 187 health problems. The average weekly prevalence of all health problems was 21.3% (95% CI: 19.2-22.9), of which 12.1% (95% CI: 10.9-13.3) constituted overuse injuries and 5.8% (95% CI: 4.6-6.9) illnesses. The incidence of acute injuries was 1.2/1000 h of tennis play (95% CI: 0.7-1.7). The high occurrence of overuse injuries among elite junior tennis players suggests that an early focus on preventative measures is warranted, with a particular focus on the monitoring and management of workload.